Doctor’s Appointment Booking System Using Recommendation Model - Raut, Rohit Vaibhav; Ghorpade, Manavi Uttam (International Journal of Computer Sciences and Engineering, 2020)
In today’s world, health is turning into the spinal cord of each individual's way of life. Suitable health check-up for various health-related problems, every individual needs a specialist Doctor to treat them appropriately. To give ease in accessing the sources to the individuals about the doctors according to their requirements and for the doctors to get ease in accessing their patients and their data, by considering these challenges the idea of this work has been advanced with the use of recommendation system. The application will be used by both; the patients as well as the doctors. The patient will Sign-In for getting the required field of service from the specialist doctors that are available and, the doctors will Sign-In for accessing the patients that are to be treated via appointments made from the application used by the patient’s side.